Cobalt(III)-Catalyzed Allylation with Allyl Acetates by C–H/C–O Cleavage - Moselage, Marc; Sauermann, Nicolas; Koeller, Julian; Liu, Weiping; Gelman, Dmitri; Ackermann, Lutz (Synlett, 2015)
Versatile cobalt-catalyzed C–H allylations on arenes, indoles, and pyrroles were accomplished with allyl acetates. The C–H/C–O functionalization process was characterized by a broad substrate scope as well as an excellent functional-group tolerance and was shown to occur by initial C–H cobaltation.
Keywords: allylation; C–H activation; C–O cleavage; cobalt; heteroarene